Diagnosis, Management, and Outcome of Stroke Infark: A Ten Years Systematic Review - Halim, Stevanie S; Zaskia, Nanda Ayu (The International Journal of Medical Science and Health Research, 2024)
Background: Treatment for Ischemic stroke has shown promising results with antiplatelet therapy and ginkgo biloba extracts, but clopidogrel and aspirin resistance may increase bleeding risk. Ticagrelor, a novel antiplatelet drug, shows efficacy. Methods: Using the PRISMA 2020 principles, this systematic review concentrated on full-text English literature published between 2014 and 2024. Among other internet resources, PubMed, ScienceDirect, and SagePub were used to compile the literature. Result: Following a thorough three-level screening process, six publications were determined to be closely connected to our current comprehensive review. Following that, an extensive examination of the entire text was carried out, and these articles were subjected to further inspection. Conclusion: Antiplatelet therapy's efficacy and safety in treating ischemic stroke are limited due to short symptom onset, high price, and low accessibility. Combining antiplatelet therapy with rt-PA for better outcomes is recommended. Neuroprotective agents like ginkgo diterpene lactone meglumine show potential for improving functional outcomes and reducing bleeding risks.